Cerebrospinal fluid cyto‐/chemokine profile during acute herpes simplex virus induced anti‐N‐methyl‐d‐aspartate receptor encephalitis and in chronic neurological sequelae. (25th April 2017) - Kothur, Kavitha; Gill, Deepak; Wong, Melanie; Mohammad, Shekeeb S; Bandodkar, Sushil; Arbunckle, Susan; Wienholt, Louise; Dale, Russell C
Abstract : Aim: To examine the cytokine/chemokine profile of cerebrospinal fluid (CSF) during acute herpes simplex virus‐induced N ‐methyl‐d ‐aspartate receptor (NMDAR) autoimmunity and in chronic/relapsing post‐herpes simplex virus encephalitis (HSE) neurological syndromes. Method: We measured longitudinal serial CSF cyto‐/chemokines ( n =34) and a glial marker (calcium‐binding astroglial protein, S100B) in one patient during acute HSE and subsequent anti‐NMDAR encephalitis, and compared the results with those from two patients with anti‐NMDAR encephalitis without preceding HSE. We also compared cyto‐/chemokines in cross‐sectional CSF samples from three children with previous HSE who had ongoing chronic or relapsing neurological symptoms (2yr 9 mo–16y after HSE) with those in a group of children having non‐inflammatory neurological conditions ( n =20). Results: Acute HSE showed elevation of a broad range of all T‐helper‐subset‐related cyto‐/chemokines and S100B whereas the post‐HSE anti‐NMDAR encephalitis phase showed persistent elevation of two of five T‐helper‐1 (chemokine [C‐X‐C motif] ligand 9 [CXCL9], CXCL10), three of five predominantly B‐cell (CXCL13, CCL19, a proliferation‐inducing ligand [APRIL])‐mediated cyto‐/chemokines, and interferon‐ α . The post‐HSE anti‐NMDAR encephalitis inflammatory response was more pronounced than anti‐NMDAR encephalitis. All three chronic post‐HSE cases showed persistent elevation of CXCL9, CXCL10, and interferon‐ α, and there was histopathological evidence of chronic lymphocytic inflammation in one biopsied case 7 years after HSE. Two of three chronic cases showed a modest response to immune therapy. Interpretation: HSE‐induced anti‐NMDAR encephalitis is a complex and pronounced inflammatory syndrome. There is persistent CSF upregulation of cyto‐/chemokines in chronic or relapsing post‐HSE neurological symptoms, which may be modifiable with immune therapy. The elevated cyto‐/chemokines may be targets of monoclonal therapies. What this paper adds: Inflammatory response is higher in anti‐ N ‐methyl‐d ‐aspartate receptor (anti‐NMDAR) encephalitis if is it preceded by herpes simplex encephalitis (HSE). Aggressive immune treatment in acute post‐HSE anti‐NMDAR illness improves the chances of a good outcome. Children with previous HSE and ongoing neurological symptoms may have persistent immune activation and chronic encephalitis. Persistent cerebrospinal fluid upregulation of cyto‐/chemokines may be modifiable with immune therapy. This article is commented on by Ellul and Griffiths on pages776–777 of this issue.